The environmental debate a documentary history, with timeline, glossary and appendices - Neimark, Peninah 1938-; Mott, Peter Rhoades; Gale Group (Amenia, N.Y. Grey House Pub., 2011)
Examines the evolution of concern about environmental degradation, pollution, and resource conservation in America from the Colonial period to the present.
pt. 1. Foundations of American environmental thought and action -- pt. 2. Politicians, naturalists, and artists in the new nation, 1776-1839 -- pt. 3. The origins of environmental activism, 1840-1889 -- pt. 4. The conservation movement era, 1890-1919 -- pt. 5. Rethinking our relationship to nature, 1920-1959 -- pt. 6. The heyday of the environmental movement, 1960-1979 -- pt. 7. Confronting economic and social realities, 1980-1999 -- pt. 8. Challenges for the twenty-first century.
Electronic reproduction.
Keywords: Environmentalism -- United States -- History -- Sources; Electronic books